How to cheat at administering Office communications server 2007 - Piltzecker, Tony, 1975-; Morimoto, Rand.; Barrett, Ronald (Burlington, MA : Syngress, 2007)
Microsoft Office Communications Server (OCS) 2007 is Microsofts latest version of Live Communications Server 2005. The product provides management for all synchronous communications that takes place in real time. This includes instant messaging (IM), Voice over IP (VoIP), and audio conferencing and videoconferencing. It will work with your companys existing telecommunications systems without major hardware upgrades. This means your business can deploy advanced VoIP and conferencing without tearing out its preexisting legacy telephone network. How to Cheat at Administering Microsoft Office Communicator 2007 provides the busy system administrator with any easy-to-access reference that provides step-by-step instructions on how to install, configure, manage and troubleshoot Communicator across the network. It is the perfect tool for those who simply need to complete a task without reading through lots of theory and principles. Get Inside Microsoft Office Communications Server 2007 Learn whats new in OCS 2007, compare the previous editions, understand OCS 2007 server roles, plan an OCS 2007 installation. Install the First OCS 2007 Front-End Server Address the prerequisites, prepare active directory, install and configure OCS 2007 Enterprise Edition, and verify the installation summary. Configure the Edge Server Install the Edge Server, work with certificates, deal with security issues, and test the Edge Server. Configure the Mediation Server Install the Configuration Server, configure dialing rules, configure users for voice functionality, and test voice functionality. Configure Archiving Address compliance requirements, understand archiving topology, and install the Archiving Server. Configure Conference Servers Understand on-premises conferencing, use on-premises conferencing, understand Microsoft RoundTable, and install conferencing. Integrate OCS with PBX and IP-PBX Systems Use a gateway, configure Cisco CallManager as a Gateway, and understand CSTA/SIP gateways. Integrate OCS with Exchange 2007 Unified Messaging Master Exchange 2007 Unified Messaging and architecture, Configure Exchange 2007 UM, and Combine OCS with Exchange 2007 UM. Upgrade to Office Communications Server 2007 Plan your migration from LCS 2005 to OCS 2007, upgrade perimeter servers, upgrade director servers, upgrade front-end servers, perform user migration, and remove LCS 2005 from the network environment.
Planning for Office Communicator 2007 -- Installation and Configuration -- Integration with Existing Directories -- Integration with Outlook and Exchange Server -- Web Conferencing -- Telephone Integration -- Working with Microsoft Office -- Instant Messaging -- Working with non-Windows clients.
Includes index.
Keywords: Client/server computing; Microsoft Office live communications server; Electronic books